2011
DOI: 10.1080/08995605.2011.590409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated With Suicides of Army Soldiers 2001–2009

Abstract: Prevalence and risk factors associated with soldiers' suicides 2001-2009 (N = 874) were examined. Army suicide rates increased from 9 per 100,000 in 2001 to 22 per 100,000 in 2009. Soldier suicides were lower than civilians from 2001 to 2007, but higher than civilians after 2007. Army suicides were disproportionately higher for men, deployment experience, and a history of a mental health diagnosis/treatment; and lower for African Americans. Many involved planning (38%), communication (21%), alcohol (19%), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 47 publications
7
70
1
1
Order By: Relevance
“…The higher odds associated with lower rank is consistent with research on self-reported suicide attempts (Nock et al, 2014) and most (Bachynski et al, 2012; Bell et al, 2010; Logan, Skopp, Karch, Reger, & Gahm, 2012; Schoenbaum et al, 2014) but not all (Black, Gallaway, Bell, & Ritchie, 2011) recent studies of suicide deaths among soldiers. Although our preliminary finding of increased risk among those entering Army service prior to the age of 21 could have important implications for targeted prevention programs, there is evidence that this finding may not persist in more complex analyses (Nock et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…The higher odds associated with lower rank is consistent with research on self-reported suicide attempts (Nock et al, 2014) and most (Bachynski et al, 2012; Bell et al, 2010; Logan, Skopp, Karch, Reger, & Gahm, 2012; Schoenbaum et al, 2014) but not all (Black, Gallaway, Bell, & Ritchie, 2011) recent studies of suicide deaths among soldiers. Although our preliminary finding of increased risk among those entering Army service prior to the age of 21 could have important implications for targeted prevention programs, there is evidence that this finding may not persist in more complex analyses (Nock et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Although the influence of deployment on adverse mental health outcomes is well supported,(Bray et al, 2010; Gadermann et al, 2012; Jacobson et al, 2008; Shen, Arkes, & Williams, 2012; Wells et al, 2010) the association of deployment with suicidal thoughts and behaviors has generated inconsistent results. (Bryan et al, 2015) Prior mental disorders are a robust predictor of both fatal(Black, Gallaway, Bell, & Ritchie, 2011) and nonfatal(Ursano, Kessler, Stein, et al, 2015) suicidal behaviors in service members, findings in line with a large body of civilian research. (Harris & Barraclough, 1997; Nock, Hwang, Sampson, & Kessler, 2010)…”
supporting
confidence: 73%
“…Such might be explained by cohort members being formally diagnosed and their conditions treated, as opposed to those with potentially undiagnosed, untreated disorders, or by the cohort's 77% decreased rate of deployment, a risk factor for suicide. 13,14 The majority of those diagnosed with most mental diagnoses did complete 48 months of service. Though completion rate was lower than for those not so diagnosed, an argument can be made for the efficacy care in terms of assisting most members with mental diagnoses to complete their tours of duty.…”
Section: Discussionmentioning
confidence: 99%